Hubungan Dukungan Keluarga Dengan Pengendalian Hipertensi Pada Lansia Di Wilayah Kerja Puskesmas Benteng Kecamatan Nusaniwe Ambon Indonesia. : Dukungan Keluarga Dengan Pengendalian Hipertensi Pada Lansia - Rumakey, Ratna Sari (Journal Kiara : Nursing and Midwifery, 2024)
Support from the family is needed in the treatment of hypertension sufferers. The family is a support system in the life of people with hypertension, so that their condition does not get worse and avoid complications due to hypertension. If people with hypertension do not prevent and treat their hypertension optimally, people with hypertension will be at risk of experiencing complications. This study was to determine the relationship between family support and hypertension control in the Benteng Health Center area, Nusaniwe District, Ambon City. This study uses a quantitative method, this type of research is analytic with a cross sectional approach. The population of this study were 80 hypertensive patients in the Benteng health center area. The sample of this research is 63 respondents. Most of the elderly received good family support, namely 38 elderly (60.3%) and most of the elderly had good hypertension control, namely 44 elderly (69.8%). The p value is 0.008, which means p <0.05 and the correlation coefficient is 1.000, which means that there is a relationship between family support and hypertension control in the elderly. Control of hypertension must at least be accompanied by a good family and also good motivation from the family. The advice given to the family is that it is hoped that the family will increase support for the elderly who suffer from hypertension, so that hypertension control is better.